State Policy, Livelihood Protection and Gender on Canada's East Coast - MacDonald, Martha; Neis, Barbara; Murray, Grant (International Journal of Canadian Studies / Revue internationale d’études canadiennes)

(untitled) (Conseil international d'études canadiennes, 2008)
This paper looks at the interactions between environmental and industrial restructuring within the Newfoundland and Labrador fishery and regime shifts in three main policy areas related to fisheries. Our focus is the gendered consequences of interactive restructuring across policy areas for the ability of women and men in fisheries households in Newfoundland and Labrador to make a living. The three main policy areas include fisheries management policy, Employment Insurance policy and policy related to the regulation of occupational health and workers compensation. We document important similarities in the overall pattern and outcomes of regime shift within these three policy areas and point to ways these changes have interacted with resource degradation and industrial restructuring to influence the lives and livelihoods of fishery dependent people.